Republic of Latvia : Request for Stand-By Arrangement; Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Latvia. (IMF Staff Country Reports; Country Report ;, 2009)
This paper discusses a request from the Republic of Latvia for a Stand-By Arrangement. The Latvian authorities are launching a decisive economic reform program and are seeking substantial international financial assistance to quell the crisis. With international reserves falling precipitously and reserves barely covering base money, the authorities are now seeking IMF assistance under the emergency financing procedures. The proposed IMF-supported program is part of a coordinated international effort. The program is centered on maintaining Latvia's exchange rate peg through strong domestic policies and substantial international financial assistance.